Prescribing and formulating neonatal intravenous feeding solutions by microcomputer. Issue 6 (June 1984) - MacMahon, P
Abstract : This paper describes a computer programme for a low cost microcomputer designed to assist in the task of administering total parenteral nutrition to neonates: no knowledge of computers is necessary to operate the system. The programme displays recommended values for each of the total parenteral nutrition constituents that must be prescribed, based on detailed analysis of all the pertinent variables. The recommended values may be rejected but they do provide a useful prompt, especially for the more junior doctors. The programme includes a number of safeguards that protect against entering potentially dangerous values. As soon as the operator has completed the procedure of entering total parenteral nutrition requirements the calculations necessary to formulate a solution containing these are automatically performed. The print out contains this data plus instructions on the infusion rate and an analysis of the formulation's calorific content. This system makes it easier to vary the quantity of individual total parenteral nutrition constituents and time has been saved which was previously wasted performing laborious calculations. One of the most important contributions has been the virtual elimination of errors in the complex task of prescribing and formulating total parenteral nutrition for sick neonates.